Masses and size distributions of mechanically fragmented microplastics from LDPE and EPS under simulated landfill conditions - Lu, Xuhong (2023)
Landfills contain significant amounts of plastic waste (PW) and microplastics (MPs). However, the contributions of various PW fragmentation processes to the quality and quantity of MPs in landfills are unclear. In this study, LDPE and EPS pieces were mixed with sand to simulate landfilled solid waste, which experienced one-dimensional abiotic compression under vertical stress of 100-800 kPa for 1-300 days. The generated MPs were stained and quantified with a fluorescent microscope. The numbers and masses of the fragmented MPs increase with the increasing compression stress and duration following linear or exponential trends. EPS has a lower stiffness than LDPE, thus generates more MPs under the same compression conditions. Stress-dependent and time-dependent fragmentation mechanisms are distinguished, the former is driven by sand-plastic porosity reduction and the latter is due to microscopic interfacial creep with minimal porosity reduction. Most of the mechanically fragmented MPs have diameters < 100 µm. The MPs size distributions follow an established power-law model, which are dependent on stress, duration, porosity reduction, and fragmentation mechanism. Our results serve as conservative estimations on long-term MPs generation in real landfills, which provide confirmative and quantitative evidence to support the previous studies reporting the varied MPs abundances and properties within landfills.